LEADERSHIP DYNAMICS OF BOARDING SCHOOLS: CASE STUDY PP. RA'IYATUL HUSNAN (SUNAN DRAJAD) - Mahtum, Imam; Mundiri, Akmal; Manshur, Umar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to discover and describe the problems of pesantren leadership case study PP. Ra'iyatul Husanan (sunan derajad) Wringin, Bondowoso. Specific objectives: 1) To know the Leadership Strategy in PP. Ra'iyatul Husanan (Sunan Derajad) Wringin, Bondowoso, 2) Kiai strategy in attracting public interest, 3) Leadership Pattern In PP. Ro'iyatul Husanan (Sunan Derajad) Wringin, Bondowoso. The results of this study show that the problem of pesantren leadership can be resolved by always following the developments that occur in society without changing the existing culture.  With the slogan "devotees become guardians" is a strategy implemented by the caregivers of the Ra'iyatul Husnan 05 Islamic Boarding School (Sunan Drajad) to attract community interest in responding to the needs and challenges that exist in the community.